Application of high viscosity bone cement in vertebroplasty for treatment of painful vertebral body fracture - Saša Rapan; Karin Krnić; Vjeran Rapan; Vjekoslav Kolarević (Medicinski glasnik, 2016)
Aim: To evaluate the effectiveness and complication of vertebroplasty with high viscosity cement (HVC). Methods: The patients with intensive pain caused by a fractured vertebrae were treated by application of HVC into the vertebral body, through unilateral transpedicular approach. The application was performed in 422 patients (221 were treated for osteoporosis and 201 for malignancy) on 846 vertebrae. Results: Preoperative Visual Analogue Scale (VAS) score was 8.35 and 2.21 (p<0.00001) 24 hours after surgery and 3 months later, respectively. There was no serious intra- and post-surgery complication. By diascopy during the surgery in 121 (14.3%) vertebrae cement leakage from the fractured vertebral body was evidenced, which did not cause any aggravation of patients’ clinical status. Conclusion: Vertebroplasty with HVC is a method that successfully combines all advantages of this method but it also minimizes the risk of extra-ossal cement leakage which makes it significantly safer for the surgeon and for the patient as well.
Keywords: bone cement; vertebral augmentation; Visual Analogue Scale